National Identity and Mixed-Race Public Figures: A Critical Discourse Analysis Study - Tjiono, Anastasya Maria; Arvianti, Indah; Ayunda, Nenin Astiti (Journal of Education Research, 2024)
The identity and nationalism of mixed-race individuals are frequently questioned. Therefore, this study aims to synthesize the national identity of Bryan Domani, Cinta Laura, and Aurelie Moeremans as mixed-race public figures using the Critical Discourse Analysis (CDA) approach. A descriptive qualitative method was used to interpret this data, wherein the researcher analyzed podcast interviews and examined Instagram posts. This study’s synthesis is divided into the background context of adapting their language skills, evaluating their cultural acceptance, and analyzing their preference for Indonesia. As a result, they experience difficulties with Indonesian proficiency due to their foreign-sounding accent. Additionally, they also demonstrate their national identity through their contribution to Indonesia.